Investigation of efficiency enhancement in InGaN MQW LED with compositionally step graded GaN/InAlN/GaN multi-layer barrier. (April 2018) - Prajoon, P.; Anuja Menokey, M.; Charles Pravin, J.; Ajayan, J.; Rajesh, S.; Nirmal, D.
Abstract: The advantage of InGaN multiple Quantum well (MQW) Light emitting diode (LED) on a SiC substrate with compositionally step graded GaN/InAlN/GaN multi-layer barrier (MLB) is studied. The Internal quantum efficiency, Optical power, current-voltage characteristics, spontaneous emission rate and carrier distribution profile in the active region are investigated using Sentaurus TCAD simulation. An analytical model is also developed to describe the QW carrier injection efficiency, by including carrier leakage mechanisms like carrier overflow, thermionic emission and tunnelling. The enhanced electron confinement, reduced carrier asymmetry, and suppressed carrier overflow in the active region of the MLB MQW LED leads to render a superior performance than the conventional GaN barrier MQW LED. The simulation result also elucidates the efficiency droop behaviour in the MLB MQW LED, it suggests that the efficiency droop effect is remarkably improved when the GaN barrier is replaced with GaN/InAlN/GaN MLB barrier. The analysis shows a dominating behaviour of carrier escape mechanism due to tunnelling. Moreover, the lower lattice mismatching of SiC substrate with GaN epitaxial layer is attributed with good crystal quality and reduced polarization effect, ultimately enhances the optical performance of the LEDs. Highlights: Multilayer barrier in the MQW design reduces the threading dislocation and improves the crystal quality. The carrier confinement in the QW is improved by the incorporation of MLB design in MQW LED structures. The SiC substrate is a good alternative for sapphire to improve the crystal structure of LEDs. Efficiency droop reduced to 2.6% at 500 mA Injection current and Light-output power increased to 1680 mW.